ABO blood groups in COVID‐19 patients; Cross‐sectional study. Issue 4 (19th December 2020) - Solmaz, İhsan; Araç, Songül
Abstract: Aim: The aim of this study was to investigate the ABO and Rh blood group distribution and clinical characteristics in patients with COVID‐19. Materials and Methods: The clinical characteristics and blood groups of 1667 patients who were hospitalised because of COVID‐19 (with a positive PCR test) between 16 March and 10 July were reviewed cross‐sectionally. Results: When blood groups of patients diagnosed with COVID‐19 and control group were compared, it was observed that there was an increase in the number of COVID‐19 patients with blood groups A and AB, decrease in the number of COVID‐19 patients with blood group O, a statistically significant increase in the number of individuals with blood group A in COVID‐19 patients compared with healthy individuals, and almost significant increase in the number of COVID‐19 patients with blood group AB and a very significant decrease in the number of COVID‐19 patients with blood group O. Conclusion: Our study has found that having blood group O may be protective, that blood group A may have greater susceptibility to the disease, but this does not affect the course of the disease and is not associated with mortality.